HUBUNGAN KEMAMPUAN TEORI DENGAN KEMAMPUAN PRAKTEK MATERI PELAJARAN SENI RUPA SISWA KELAS VII SMP NEGERI 12 PADANG - Namira, Drs. Eswendi, M.Pd, Drs. Yusron Wikarya, M.Pd (Universitas Negeri Padang, 2013)
The purposes of this research were to describe the connection between the theoretical capability with the ability to practice the subject matter of visual art class VII student of SMP Negeri 12 Padang. This type of research is correlational research with quantitative research approaches. The technique data was collected with engineering documentation. Data collection tool is a documentation sheet. The data that processed with descriptive techniques and Pearson product moment correlation. Index of correlation (rxy) table of 0.474 (KD = 22.5%) < rxy count of 6.612. It means that the presence of a significant positive connection between the ability of theory with practical skills in the degree 05%. Key word: Theoretical ability; practical ability; visual art; sum.